The The Role of the Intervention Community in Participating to Overcome the Problem of Fulfilling the Right to Education in Surabaya - Tsani, Syafa Amalia; Sari, Maya Mustika Kartika (Kajian Moral dan Kewarganegaraan, 2024)
The issue of educational rights fulfillment in Surabaya is a social problem arising from discrepancies within the existing educational system. Although the government is responsible for addressing this issue, its implementation remains limited and suboptimal. This study aims to evaluate the role of the Turun Tangan Surabaya community in addressing the problem of educational rights fulfillment in the city. The research employs a qualitative method with a case study design, involving the collection of primary data through interviews and secondary data through documentation. The collected data is analyzed using the AGIL scheme within Talcott Parsons' structural functional theory. The findings reveal that the Turun Tangan Surabaya community plays a significant role in fulfilling educational rights through several approaches. First, they provide manpower support through activities such as "Tebar Senyum," focusing on motivating and emotionally supporting students. Second, they offer educational services by organizing events like the School People's Olympics, aimed at enhancing educational quality. Third, the community supports literacy by conducting activities like "book story" and literacy contributions to provide reading materials and foster a reading culture. Fourth, they encourage community participation in their activities to increase public involvement and support for education. This study highlights that the community's active role in various aspects significantly impacts the fulfillment of educational rights in Surabaya